Pseudophoxinus cilicicus, a new spring minnow from southern Anatolia (Teleostei: Leuciscidae) - Saç, Gülşah; Özuluğ, Müfi̇t; Geiger, Matthias F.; Freyhof, Jörg (Zootaxa, 2019)
Pseudophoxinus cilicicus, new species, is described from the Arsuz, Ceyhan and Seyhan river drainages in the Gulf of İskenderun. It is distinguished from other members of the Pseudophoxinus zeregi species group by having a complete lateral line with 38–45 + 2–3 scales, the lower lip usually slightly projecting beyond the tip of the upper lip, a prominent black stripe along the flank, and no black pigments below the lateral line. Pseudophoxinus cilicicus is distinguished from P. zekayi by a minimum K2P distance of 3.8% based on the mitochondrial DNA barcode region. Pseudophoxinus atropatenus and P. sojuchbulagi are returned to the genus Rutilus.